2018
DOI: 10.1371/journal.pone.0206731
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the serum albumin level on acute kidney injury after cerebral artery aneurysm clipping

Abstract: BackgroundAlthough hypoalbuminemia is a known risk factor for acute kidney injury (AKI) following surgery, little is known about its effects following aneurysm clipping surgery. We aimed to investigate the predictors of AKI and overall mortality and assessed the relationship between preoperative albumin and postoperative outcomes after aneurysm clipping surgery.MethodsThis study included 2,339 patients who underwent aneurysm clipping surgery. According to the criteria updated by the Kidney Disease: Improving G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Finally, it has been reported that elevated RDW is associated with malnutrition 36. And hypoalbuminemia, a marker of malnutrition, is an independent risk factor of AKI in various clinical settings [37][38][39]. Therefore, malnutrition is another bridge to understand the relationship between elevated RDW and AKI.Previous studies had explored the prognostic value of RDW in TBI patients with contradictory results.…”
mentioning
confidence: 99%
“…Finally, it has been reported that elevated RDW is associated with malnutrition 36. And hypoalbuminemia, a marker of malnutrition, is an independent risk factor of AKI in various clinical settings [37][38][39]. Therefore, malnutrition is another bridge to understand the relationship between elevated RDW and AKI.Previous studies had explored the prognostic value of RDW in TBI patients with contradictory results.…”
mentioning
confidence: 99%
“…Serum albumin is related to cerebral ischemia ( Turhan et al, 2006 ), Alzheimer’s disease ( Skillbäck et al, 2017 ; Bode et al, 2018 ; Kim et al, 2020 ), Crohn’s disease ( Su et al, 2019 ), liver cirrhosis ( Chen et al, 2011 ; Oettl et al, 2013 ; Arroyo et al, 2014 ), chronic heart failure ( Jabbour et al, 2014 ), acute kidney injury ( Bang et al, 2018 ; Thongprayoon et al, 2018 ; Lv et al, 2021 ), chronic kidney disease ( Stoycheff et al, 2009 ; Zhang et al, 2015 ) and other diseases; however, the relationship between serum albumin and pulmonary function is unclear. Several studies have shown that in some acute respiratory diseases that lead to reduced pulmonary function, such as acute respiratory distress and acute lung, serum albumin increases capillary permeability, causing it to leak from blood vessels into tissue fluid or to escape into the alveolar space, resulting in reduced serum albumin levels ( Fanali et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Low preoperative serum albumin levels are associated with perioperative complications including AKI [ 23 ]. Albumin is a potential natural antioxidant that acts as a core extravascular source of reduced sulfhydryl groups, so-called thiols, that scavenge reactive oxygen and nitrogen species; thus, hypoalbuminemia can cause postoperative AKI [ 24 ].…”
Section: Discussionmentioning
confidence: 99%